Repealing Ireland's Eighth Amendment: abortion rights and democracy today. (7th September 2020) - Drążkiewicz, Ela; Strong, Thomas; Scheper‐Hughes, Nancy; Turpin, Hugh; Saris, A Jamie; Mishtal, Joanna; Wulff, Helena; French, Brigittine; Garvey, Pauline; Miller, Daniel; Murphy, Fiona; Maguire, Louise; et al.
Abstract : In 2018, the Irish public voted to repeal the Eighth Amendment to the Irish Constitution, which since 1983 banned abortion in the country. While this was a watershed moment in Irish history, it was not unconnected to wider discussions now taking place around the world concerning gender, reproductive rights, the future of religion, Church–State relationships, democracy and social movements. With this Forum, we want to prompt some anthropological interpretations of Ireland's repeal of the Eighth Amendment as a matter concerning not only reproductive rights, but also questions of life and death, faith and shame, women and men, state power and individual liberty, and more. We also ask what this event might mean (if anything) for other societies dealing with similar issues? L'abrogation du huitième amendement de la Constitution irlandaise : le droit à l'avortement et la démocratie aujourd'hui: En 2018, le peuple irlandais a voté l'abrogation du huitième amendement de la Constitution irlandaise interdisant l'avortement dans le pays depuis 1983. L'Irlande vivait alors un moment décisif de son histoire, qui n'était pas sans lien avec de plus vastes débats, aujourd'hui en cours dans le monde entier, portant sur le genre, le droit à la procréation, l'avenir de la religion, les relations entre l'Église et l'État, la démocratie et les mouvements sociaux. Dans ce Forum, nous voulons encourager une lecture anthropologique de l'abrogation du huitième amendement par l'Irlande, car elle concerne non seulement le droit à la procréation, mais aussi la vie et la mort, la foi et la honte, les femmes et les hommes, le pouvoir étatique, la liberté individuelle et plus encore. Nous nous interrogeons également sur la signification que cet événement pourrait avoir (s'il en a une) aux yeux d'autres sociétés traversées par des questions analogues.